Academic Research School of Administrative Law - M. N. Kobzar-Frolova; A. A. Grishkovets (Сибирское юридическое обозрение)
This article examines the academic research school of administrative law, highlighting its importance within the scientific community. An academic school is understood as a cohesive local community of scholars united by a common idea, which forms part of the larger professional scientific community. Key features of a scientific school are outlined, including the presence of distinct research directions, which are typically defined by the scientific interests and expertise of the most influential members of the school. The origins and development of the academic research school of administrative law, founded by Professor Semyon Sevast’yanovich Studenikin, are explored. The article analyzes Studenikin’s foundational ideas that shaped this school and highlights areas of particular interest to him. A brief overview of the scientific achievements of the school’s representatives, which developed and continues to flourish at the Institute of State and Law of the Russian Academy of Sciences, is provided. Three main research areas within this scientific school are identified: theoretical, public-administrative, and the protection of citizens’ subjective rights in the field of public administration. The first two areas were developed by Professor S.S. Studenikin, while the third was pioneered by Professor M.D. Zagryatskov. The contributions of the followers of these scholars, including contemporary academics, to each of the three primary directions of the school are also discussed.